OCCURRENCE OF INTESTINAL PARASITES IN FECAL SAMPLES OF DOGS AND CATS FROM MINEIROS, GOIÁS - MARTINS, A. P.; DUARTE, R. B.; SILVA, M. F. S.; SOARES, J. M.; BRAGA, I. A.; RAMOS, D. G. S. (Ars Veterinaria, 2022)
Gastrointestinal parasites are frequently found in domestic animals, with important role in animal and public health. Among gastrointestinal parasites of dogs and cats Toxocara spp. and Ancylostoma spp. are reported as the most common parasites found in dogs and cats in the world caunsing digestive damage, including death, and with great importance in public health causing visceral larva migrans and cutaneous larva migrans respectively. This study aimed verify the occurrence of gastroenteric parasites in dogs and cats from Mineiros, Goiás, in association with epidemiological aspects. In total, 103 fecal samples (93 from dogs and 10 from cats) from April 2017 to July 2018 were collected by spontaneous defecation and processed for search of eggs and oocysts by the Willis (adapted) technique. Toxocara spp. was the most frequent parasite identified in dogs, with 34.41% frequency (32/93 samples), followed by Ancylostoma spp. (11.83%, 11/93 samples) and Cystoisospora spp. (1.07%, 1/93 samples). Fecal samples from cats, showed a similar result, being Toxocara spp. the most frequent parasite (40%, 4/10 samples), followed by Ancylostoma spp. (20%, 2/10 samples) and Cystoisospora spp. (20%, 2/10 samples). Young animals were 10% more positive for parasites comparing to elderly and adult animals (odds ratio=1.1), as well as animals with access outdoors 20% more parasitized (odds ratio=1.2). The study showed the most common gastrintesinal parasites of dogs and acts from Mineiros, Goiás.